2019
DOI: 10.1063/1.5087098
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hole-extraction in carbon-electrode based planar perovskite solar cells by moisture-assisted post-annealing

Abstract: Moisture-assisted post-annealing was performed on carbon-electrode based planar perovskite solar cells so as to improve the hole-extraction process. It was observed that, after being annealed at a relative humidity of 30% for 2 h, the short-circuit current density, fill factor, and open circuit voltage were all improved, leading to an improvement of 21.75% of power conversion efficiency [from 10.53 (±0.98)% to 12.82 (±1.07)%, with the optimized one at 14.77% for reverse scanning]. The transient photovoltage/ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 29 publications
3
49
0
1
Order By: Relevance
“…[266] Hu et al developed a 10-serially connected module (10 × 10 cm 2 , 49 cm 2 active area) with a PCE of 10.4%, showing a light-soaking stability of 1000 h, a local outdoor stability of 1 month and a shelf-life stability of over 1 year. [267] Baranwal et al also demonstrated sealed meso CPSCs could kept >90% of the initial PCE after heated at 100 °C for 4500 h. [268] Different from meso CPSC, the carbon electrodes are deposited after the deposition of perovskite layers followed by annealing at a low temperature like 100 °C for planar CPSCs. The highest PCE for planar CPSCs of 19.2% was achieved by Zhang et al Their devices retained 95% of the initial PCE after 1000 h storage in ambient condition.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 99%
“…[266] Hu et al developed a 10-serially connected module (10 × 10 cm 2 , 49 cm 2 active area) with a PCE of 10.4%, showing a light-soaking stability of 1000 h, a local outdoor stability of 1 month and a shelf-life stability of over 1 year. [267] Baranwal et al also demonstrated sealed meso CPSCs could kept >90% of the initial PCE after heated at 100 °C for 4500 h. [268] Different from meso CPSC, the carbon electrodes are deposited after the deposition of perovskite layers followed by annealing at a low temperature like 100 °C for planar CPSCs. The highest PCE for planar CPSCs of 19.2% was achieved by Zhang et al Their devices retained 95% of the initial PCE after 1000 h storage in ambient condition.…”
Section: Stable Nonmetal Electrodes As Barriersmentioning
confidence: 99%
“…Then, the half device is immersed into MAI solution (“MAI bath,” MAI represents CH 3 NH 3 I) so as to convert the pre‐coated PbI 2 into PVSK . Besides the merit of the low cost of carbon materials, two more merits are also shared by these CPSCs: the first one is the compatibility with scaling fabrication techniques, such as screening‐printing and inkjet‐printing; and the second one is the featured, micrometer‐sized thickness of the carbon‐electrode . This feature, along with the inert nature of the carbon materials, could contribute to device stability.…”
Section: Main Features Of Cpscsmentioning
confidence: 99%
“…Thus, hole‐transporting‐material (HTM, or hole‐transport‐layer/HTL), on which metal‐electrodes‐based PSCs (noted by metal PSCs) are usually relied, is not necessarily used in CPSCs, leading to HTM‐free devices . From the pioneered works done by Han, Yang, Zhao, and coworkers, CPSCs have attracted ever‐increasing attention . As long as the formation process of PVSK is considered, four kinds of architectures have been adopted: meso CPSCs, embedment CPSCs, planar CPSCs, and quasi‐planar CPSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic-inorganic hybrid perovskites have attracted significant interest in solution processed high-performance optoelectronic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Besides the great success in photovoltaics, their unique optical and electrical properties make hybrid perovskites promising candidates for next generation light emitting diodes (LEDs) [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%